2018
DOI: 10.1111/jnc.14462
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts in the neuropathogenesis of mucolipidosis type IV

Abstract: Mucolipidosis type IV (MLIV) is an autosomal recessive, lysosomal storage disorder causing progressively severe intellectual disability, motor and speech deficits, retinal degeneration often culminating in blindness, and systemic disease causing a shortened lifespan. MLIV results from mutations in the gene MCOLN1 encoding the transient receptor potential channel mucolipin-1. It is an ultra-rare disease and is currently known to affect just over 100 diagnosed individuals. The last decade has provided a wealth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 163 publications
(260 reference statements)
3
40
0
Order By: Relevance
“…Similarly to TFEB-induced secretion, we find that the secretory pathway elicited by cyclodextrin depends on the endo/lysosomal calcium channel MCOLN1, which is responsible for the LSD mucolipidosis type 4 when mutated (Boudewyn and Walkley, 2018). Previous studies showed that MCOLN1 is involved in the secretion of endo-lysosomal content, since secretion is impaired in MCOLN1 mutant cells (LaPlante et al, 2006), and stimulated by activating MCOLN1 mutations (Dong et al, 2009).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similarly to TFEB-induced secretion, we find that the secretory pathway elicited by cyclodextrin depends on the endo/lysosomal calcium channel MCOLN1, which is responsible for the LSD mucolipidosis type 4 when mutated (Boudewyn and Walkley, 2018). Previous studies showed that MCOLN1 is involved in the secretion of endo-lysosomal content, since secretion is impaired in MCOLN1 mutant cells (LaPlante et al, 2006), and stimulated by activating MCOLN1 mutations (Dong et al, 2009).…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, storage in cells from NPC and other LSDs can be reverted by δ-Tocopherol treatment (Xu et al, 2012) or activation of BK channels (Zhong et al, 2016), which also promote endo/lysosome-mediated secretion. Interestingly, the secretion of endo/lysosome storage materials seems to depend on the activation of the lysosomal cation channel mucolipin-1 (MCOLN1), which is itself responsible for the LSD mucolipidosis type 4 when mutated (Boudewyn and Walkley, 2018). Endosome-or lysosomes-mediated secretion is impaired in MCOLN1 mutant cells (LaPlante et al, 2006), while activating mutations in the channel increase the rate of this exocytic pathway (Dong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in MCOLN1 disrupt many cellular functions and cause neurodevelopmental disorders by unknown mechanisms. Mucolipin1 is involved in the regulation of fusion/fission of vesicles along the endocytic pathway and in some aspects of the lysosomal Ca 2+ homeostasis [144,145]. Biochemical studies indicate that ML IV-patients suffer from a deficient sialidase activity hydrolyzing gangliosides GM3 and GDla, and an increased urinary excretion of glycolipids and phospholipids [146,147].…”
Section: Mucolipidosis IV (Mucolipidin 1 Deficiency)mentioning
confidence: 99%
“…Many of the LSDs are associated with significant central nervous system (CNS) pathology, whereas others primarily affect peripheral organs. This Special Issue highlights some of the LSDs that impact the CNS (Bosch and Kielian ; Boudewyn and Walkley ; Burkovetskaya et al . ; Cho et al .…”
mentioning
confidence: 99%
“…This Special Issue concludes with a comprehensive synopsis on the neuropathogenesis of mucolipidosis type IV (MLIV) by Boudewyn and Walkley (Boudewyn and Walkley ). MLIV is caused by a mutation in the transient receptor potential channel mucolipin‐1, which is primarily localized to the membrane of late endosomes and lysosomes.…”
mentioning
confidence: 99%